Evaluation of energy spectrum CT for the measurement of thyroid iodine content. Issue 1 (December 2016) - Shao, Weiguang; Liu, Jingang; Liu, Dianmei
Abstract Background This study aims to provide a reference for the diagnosis of iodine deficiency disorder by evaluating the normal thyroid iodine content by energy spectrum computed tomography (CT) and calculating the iodine content ratio of thyroid to sternocleidomastoid. Methods The thyroid glands of 226 patients were scanned by energy spectrum CT, and the images were analyzed using the GSI Viewer software. Based on the imaging findings, the iodine levels of the thyroid lobes as well as the bilateral sternocleidomastoids were evaluated, and their iodine content ratios were calculated. Results No statistically significant difference was found in the thyroid iodine content between the left and right thyroid lobes (p  > 0.05). However, there was a significant difference in the thyroid iodine content between men and women (p  < 0.01). Additionally, the thyroid iodine content was found to decrease gradually with age. The iodine content ratio of thyroid to sternocleidomastoid was 96.6271 ± 33.2442. Conclusion Gemstone energy spectrum CT can be used for the measurement of thyroid iodine content in the human body. It can play a significant role in the diagnosis of iodine deficiency disorder.